PENGARUH PENARAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK SMPN 4 PADANG - Annisa Maulidia (Departemen Matematika, 2019)
Thestudent lunderstandingsmathematical iconcept ability is one of ithe mathematicslearning goals that are expected to be archived by students. However, the understanding mathematical concept ability of SMPN 4 Padang students is not as expected. There are some effort that could be used to improve students understanding mathematical concept ability.One of them by applying cooperatives learning model type Numbered Heads Together (NHT). The aims of this study was to describe whether the understanding mathematical concept ability of students learning by using the cooperatives learning model type NHT better than the studentsx who learn usings conven-tional learningmodel. This research typewas quasi-experimental with the research designs usinglStatich Groupd Design. The resulte show that the understanding mathematical conceptd ability of students who learn using the cooperatives learning modeltype NHT has increase. Furthermore, based con the resultl of the hypothesis test, it is find that the understanding mathematical concept ability of students who learnusing the cooperatives learning model type NHT model are better than the understanding mathematical concept ability of students who learn using the conventional learning model. So, it can be conclude that the cooperatives learning model type NHT has an influence on students understanding mathematical concepts ability.Keywords—Cooperative Learning, Numbered Heads Together Model, Understanding Mathematical Concept Ability